2003
DOI: 10.1161/01.str.0000077926.49330.64
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Gene Polymorphism and Carotid Artery Wall Thickness

Abstract: Background and Purpose-Many studies have investigated the association between the angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism and carotid artery intima-media thickness (IMT); however, most studies were small and conducted in selective samples. The aim of this study was to evaluate this association by performing a meta-analysis on published articles. Methods-We searched Medline for articles studying the association between the ACE I/D polymorphism and carotid IMT. Twenty-six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 44 publications
4
58
0
2
Order By: Relevance
“…23,24 In the general population, the ACE I/D D allele has been related to cardiovascular mortality in several meta-analyses, although such association was not duplicated by others. [25][26][27] Our recent studies found that patients with the ACE I/D gene D allele and AT1R gene A1166C C allele in RAS genes were more likely to develop DHF. 28,29 In this study, we demonstrated that the ACE I/D gene D allele and AT1R gene A1166C C allele were associated not only with the development of DHF but also with the long-term prognosis.…”
Section: Survival Free Of Death From Cardiovascular Eventsmentioning
confidence: 97%
“…23,24 In the general population, the ACE I/D D allele has been related to cardiovascular mortality in several meta-analyses, although such association was not duplicated by others. [25][26][27] Our recent studies found that patients with the ACE I/D gene D allele and AT1R gene A1166C C allele in RAS genes were more likely to develop DHF. 28,29 In this study, we demonstrated that the ACE I/D gene D allele and AT1R gene A1166C C allele were associated not only with the development of DHF but also with the long-term prognosis.…”
Section: Survival Free Of Death From Cardiovascular Eventsmentioning
confidence: 97%
“…36,37 Furthermore, several studies and metaanalyses of ACE and Atg polymorphisms demonstrate significant ethnic heterogeneity, with stronger associations of the D allele or DD genotype in Asian compared to Caucasian populations. 17,18,38 It is also possible given the retrospective study design that there may have been some selection bias due to decreased survival in patients with genotypes associated with higher RAS activity. This has been previously suggested in both a predialysis and dialysis population.…”
Section: Ras Gene Polymorphisms and Lupus Nephritismentioning
confidence: 99%
“…The insertion or deletion (I/D) of a 287-bp-long Alu repeat element in the intron 16 of this gene was proven associated with the altered levels of circulating ACE enzyme (Rigat et al 1990) as well as with cardiovascular pathophysiologies (Cambien et al 1992;Jeunemaitre et al 1992a;Keavney et al 1995). Some of the conducted studies showed positive association of DD genotype and increased risk of myocardial infarction and atherosclerosis (AgerholmLarsen et al 2000;Sayed-Tabatabaei et al 2003). However, a great number of studies, including metaanalyses, associating ACE I/D with hypertension (HT), cardiomyopathy, and coronary arthery disease showed controversial results (Jeunemaitre et al 1992bLindpaintner et al 1995;Staessen et al 1997;Sharma 1998;Dikmen et al 2006;Xu et al 2008;VaisiRaygani et al 2010).…”
mentioning
confidence: 99%